A DIC-assisted fringe projection profilometry for high-speed 3D shape, displacement and deformation measurement of textured surfaces. (July 2021) - Wu, Zhoujie; Guo, Wenbo; Pan, Bing; Kemao, Qian; Zhang, Qican
Highlights: Our recently proposed robust and high-efficiency 3D shape measurement method based on Gray codes is adopted as the base technique for the proposed DIC-assisted FPP. This base system is able to obtain a new 3D result of discontinuous textured surfaces with every four projected patterns, which efficiently provides the fundamental 3D coordinate information of the measured object for further displacement or deformation calculation at a frame rate of 542 fps. The modulation-based, robust and high-quality texture map extraction method is proposed to avoid the influence by the variation of ambient light. We further propose to use the obtained texture map to accurately and reliably match surface points at different time instants using DIC, which can realize the full-field 2D points tracking with sub-pixel accuracy. The simultaneous 3D displacement or deformation is calculated for the corresponding 2D points at different time instants, which is more reasonable than those at the same pixel location but may no longer corresponded due to in-plane object displacement or deformation. Abstract: High-speed three-dimensional (3D) shape measurement techniques based on fringe projection profilometry (FPP) have undergone huge advances over the past two decades. However, accurate 3D displacement mapping and deformation analysis of dynamic scenes using FPP remains an unsolved problem. Because fringe patterns are projected rather than attached on the tested surfaces, the full-field point-to-point correspondence cannot be accurately established between any two 3D shape results. To deal with this challenge, a DIC-assisted FPP for high-speed 3D shape, displacement and deformation measurement of textured surfaces is proposed. Firstly, a high-speed 3D shape measurement system is adopted using our recently proposed robust and efficient Gray-coded coding strategy, which can accurately reconstruct full-field shape of discontinuous surfaces with rich texture information. Then, the modulation-based method is proposed to retrieve high-quality texture map from three phase-shifting fringe patterns, which can eliminate the adverse influence of the nonuniform and time-varying ambient light. By matching the retrieved surface texture images at difference states using DIC, accurate point tracking between the measured 3D shape data can be fulfilled, leading to precise 3D displacement and deformation measurement. Experiments have verified that the proposed method can achieve 3D shape, displacement and deformation measurement of dynamic scenes at a frame rate of 542 fps without any extra expense of hardware or calibration for the FPP system. The presented method is reliable and promising for further 3D displacement mapping and deformation analysis of dynamic scenes using FPP.